2018
DOI: 10.1039/c8sc02609b
|View full text |Cite
|
Sign up to set email alerts
|

Charge carrier injection and transport engineering in two-dimensional transition metal dichalcogenides

Abstract: This review intertwines current engineering strategies tailoring the carrier injection and carrier transport of two-dimensional transition metal dichalcogenides toward efficient electronic devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
121
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(122 citation statements)
references
References 215 publications
(248 reference statements)
1
121
0
Order By: Relevance
“…This result was expected because when a bulk material is downsized to atomically thin dimensions, a strong correlation between the surface states (or traps) and charge carriers would significantly impair the mobility of free charges. [ 15 ] It has also been reported that the band gap of atomically thin ZnO increases up to 4.0 eV, becoming more insulating. [ 16 ]…”
Section: Figurementioning
confidence: 99%
“…This result was expected because when a bulk material is downsized to atomically thin dimensions, a strong correlation between the surface states (or traps) and charge carriers would significantly impair the mobility of free charges. [ 15 ] It has also been reported that the band gap of atomically thin ZnO increases up to 4.0 eV, becoming more insulating. [ 16 ]…”
Section: Figurementioning
confidence: 99%
“…In this sense, as shown in the present work, it is important to design the conducting layer carefully such that it is energetically well-matched to enable a feasible carrier transport from the photoelectrodes. Regardless of the recent monumental findings allowing high STC% using a multi-junction device 15,20 , the interface energy barrier design, has not been well identified and optimized for redox cell applications, whereas it has been well-studied in PEC water splitting community 31,40 . Specifically, this puts emphasis that choosing an appropriate conductivity type of the electrode surface upon combination with high work function conductors, such as Pt and C, is of great importance for minimizing the reaction overpotential.…”
Section: Photoelectrochemical Behaviour and Efficiency Loss Analysismentioning
confidence: 99%
“…Electronic and spin transport [82][83][84][85] in TMDCs is becoming an important topic. It has been shown that the carrier mobility increases with the number of TMDC layers 69,84 , due to reduced Coulomb scattering in thicker samples 86 , while phonon scattering limits the room temperature mobility 85 .…”
Section: Introductionmentioning
confidence: 99%